The power of attraction in the pragmatic level at the functional theory (Raparin Journal of Humanities (RJH), 2023)
The title of the research is (The power of attraction in the pragmatic level at the functional theory), the research method is (analytical description), and we have taken the research materials from the everyday language of people. The importance of this study is that it highlights the process of attraction at one of the most important levels of language, the pragmatic level within the framework of function theory, which speakers constantly resort to in everyday life in order to express their meanings and intentions. This research is divided into two parts, the first part is (the force of attraction in the act of speaking), which we have explained this process theoretically, in this section we have discussed the factors affecting the force of attraction among speakers It is in the process of attractive force. The second section is entitled (Attraction at the Pragmatic Level Related to Function Theory). In this section, we have focused on these topics (Function Theory, Schools of Function Theory, Principles of Function Theory, Attraction from the Perspective of Function Theory). We have worked hard on it.   The conclusions of this study showed that the Language is a major factor in the process of attraction, and attraction is an intentional act used by the speaker for a specific purpose A number of important factors such as (psychological, religious, political, etc.) are done for the success of the process. Attraction can be used positively or negatively, attraction can be in the interest of the agent and the agent, or vice versa. The theory of the function of attraction is one of the most important functions of language, which can be used by the speaker to influence the other person. Linking words, sentences and expressions to the environment is considered a major step to create a message effect on the other person, and a point to link the process of attraction to the pragmatic level, because the environment is a basis of pragmatic principles They depend on the context of use, as task theory has also pointed out.